”INTERNAL CONTROL”, SYSTEM OR FORMALITY” - Anto Fani , Anam; Djasuli, Mohamad (JURNAL EKBIS, 2024)
This article aims to find out how much effort is being made to realize the internal control system within the scope of IDIA (Institut Dirosat Islamiyah Al-amien) based on data collected from interviews with the chancellor, warek, dean, SPI (which is still part of the BPK), and going home. This information is important to research and convey so that the public or prospective students who will enroll in tertiary institutions know that there is an internal control system in every company, including universities, and that the internal control system must operate as it should. Apart from that, IDIA's background as a tertiary institution under the auspices of the Islamic boarding school foundation, where Islamic boarding schools are educational institutions known for their very strict internal control, especially in the human resources sector, is interesting to research as a reflection for other universities whose internal control is still lacking. weak, or even just lack of responsibility (formality).